AURORASAURUS: Citizen Science, Early Warning Systems and Space Weather - Tapia, Andrea; LaLone, Nicolas; MacDonald, Elizabeth; Hall, Michelle; Case, Nathan; Heavner, Matt (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
We have created Aurorasaurus, a website, a mobile application and a scientific tool that allows a community of users to better predict sightings of the aurora borealis. Aurorasuarus combines limited space weather science data, participant sightings and the analysis of social media data into a better prediction engine. This then serves to alert interested parties as to nearby sightings.